Efeitos da faixa de amplitude e do autocontrole de conhecimento de resultados no controle e na aprendizagem motora - Madson Pereira Cruz (2023)
During learning isometric force control there is a need to receive knowledge of results (KR). One of the ways to manipulate the moment to provide the KR is with the bandwidth (BW), which is the stipulation of a margin of tolerance for error and the provision of KR only happens if the error goes beyond the pre-established margin. The main feature of BW is that the provision of KR is based on the participant's performance. The KR provided when performance goes beyond the stipulated range (bad attempts) is interpreted as the best time to provide KR. The other way of providing KR is self-controlled (SC), which lets the participant decide when they want to receive the KR, which is contrary to BW. Studies that investigated these forms of KR provision did not analyze how these two forms of KR provision influence the predominance of motor control (MC) mechanisms. The objective of this thesis was to investigate the effects of BW and SC on motor control and learning. 36 right-handed participants, inexperienced in the task, participated in the study. The task in all experiments consisted of achieving and maintaining control of 40% of the maximum isometric force of the elbow flexor muscles in an interval of 500 ms. The study was organized into three experiments. Experiments I and II investigated BW and KR SC respectively and were composed of a stabilization phase, characterized by reaching the criterion performance of 3 consecutive attempts, the corresponding error was 10% of RMSE and the KR was provided with a frequency of 33% and an experimental condition phase, with 10 trials in each condition with the start order counterbalanced across participants. The experimental conditions were: a) BW10% and b) BW0% in experiment I, and a) KR SC and b) yoked in experiment II. In experiment III, the two forms of KR supply, BW and SC, were investigated in an acquisition phase with 2 groups: BW10% and self-controlled paired with the respective BW group (SCP), which performed 300 attempts. After 24 hours there was a retention test with 15 attempts without KR and after 5 minutes a transfer test, with the new goal of reaching 20% with 15 attempts and without KR. Data were organized into blocks of 10 exp trials. I and II, and blocks of 15 attempts exp III and the mean and standard deviation of the RMSE were calculated as a measure of performance and the time to peak force and number of corrections (NC) as measures of control mechanisms. The results showed in experiment I, that for performance to present greater precision and consistency, BW led participants to prioritize the mechanism via feedback. In experiment II, for performance to be more accurate, the SC led participants to prioritize the mechanism via pre-programming, as there was no need to change the planning of the previous attempt. In experiment III, BW is better than SC in both the gain in consistency and accuracy of performance with the change to the mechanism via feedback. Altogether, the results confirm that BW leads to more consistent and accurate performance with the predominant use of the mechanism via feedback and the SC does not come close to the performance of BW with the predominant use of the pre-programming mechanism.